PERANAN TATA KELOLA SEBAGAI MEDIASI PENGARUH CHANNEL TERHADAP PENINGKATAN PRODUKTIVITAS INDUSTRI KECIL MENENGAH (IKM) DI SIDOARJO - Luqman Hakim; Laily Muzdalifah (Journal of Research and Technology, 2018)
Small and Medium Industries (SMEs) has a very important contribution of creating jobs, which in the end can help increase people's economy in Indonesia. However, SMEs tend to care less about long-term development strategies and more care abouthow to survive today. In order to survive and develop, SMEs needs to increase their productivity. Governance improvement is one strategy to increase the productivity. Many things can affect the governance, one of which is channels. In this study, there will be discussed about the effects of channels on influencing governance to improve the productivity of SMEs. The method used to determine the effect of channels on governance is Partial Least Square (PLS). Based on the results of the discussion in thisstudy, it can be concluded that the channel has a positive influence on the governance of SMEs. Keywords: Channel, SMEs, PLS.